H NMR metabolic fingerprinting to probe temporal postharvest changes on qualitative attributes and phytochemical profile of sweet cherry fruit - Goulas, Vlasios; Minas, Ioannis S.; Kourdoulas, Panayiotis; Lazaridou, Athina; Molassiotis, Athanassios; Gerothanassis, Ioannis P.; Manganaris, George A. (My University, 2015)
Sweet cherry fruits (Prunus avium cvs. ‘Canada Giant’, ‘Ferrovia’) were harvested at commercial maturity stage and analyzed at harvest and after maintenance at room temperature (storage at ~20°C, shelf life) for 1, 2, 4, 6, and 8 days, respectively. Fruit were initially analyzed for respiration rate, qualitative attributes and textural properties: ‘Canada Giant’ fruit were characterized by higher weight losses and stem browning index, being more intense over the late stages of shelf life period; meanwhile ‘Ferrovia’ possessed appreciably better performance even after extended shelf life period. A gradual decrease of respiration rate was monitored in both cultivars, culminated after 8 days at 20°C. The sweet cherry fruit nutraceutical profile was monitored using an array of instrumental techniques (spectrophotometric assays, HPLC, 1H-NMR). Fruit antioxidant capacity was enhanced with the progress of shelf life period, concomitant with the increased levels of total anthocyanin and of phenolic compounds. ‘Ferrovia’ fruit presented higher contents of neochlorogenic acid and p-coumaroylquinic acid throughout the shelf life period. We further developed an 1H-NMR method that allows the study of primary and secondary metabolites in a single running, without previous separation and isolation procedures. Diagnostic peaks were located in the aliphatic region for sugars and organic acids, in the aromatic region for phenolic compounds and at 8.2–8.6 ppm for anthocyanins. This NMR-based methodology provides a unifying tool for quantitative and qualitative characterization of metabolite changes of sweet cherry fruits; it is also expected to be further exploited for monitoring temporal changes in other fleshy fruits.
Keywords: Antioxidants; Metabolic profile; Mechanical properties; Prunus avium; Nuclear Magnetic Resonance; Postharvest physiology